Anticoagulant activities in salivary glands of tabanid flies. - Kazimírová, M; Sulanová, M; Trimnellt, A; Kozánek, M; Vidlicka, L; Labuda, M; Nuttall, P (2002)
Tabanid flies are telmophages (pool feeders), taking frequent and rapid bloodmeals from many different individual hosts. To investigate how they accomplish this intermittent feeding strategy, we examined the anticoagulant activities in salivary gland extracts (SGE) from 19 species representing six genera: Atylotus, Chrysops, Haematopota, Heptatoma, Hybomitra and Tabanus (Diptera: Tabanidae). Standard coagulation screen assays were used to determine thrombin time, prothrombin time and activated partial thromboplastin time. Chromogenic substrate assays were performed for thrombin and factor Xa activity. SGE of most species (except Chrysops spp.) considerably prolonged human plasma clotting time in a dose-dependent manner, and showed potent and specific antithrombin activity in the chromogenic substrate assay. Heptatoma pellucens displayed the strongest anticoagulant activity. Specific anti-factor Xa activity in tabanid SGE was not detected. Electrophoretic profiles of SGE proteins differed between genera and species. Overall, the results suggest that tabanids have evolved at least two antihaemostatic strategies.